LEARNING CULTURE OF ISLAMIC BOARDING SCHOOL STUDENTS - Arifudin, Moch.; Basuki, Agus; Rukhana, Elya; Rahmah, Mawadah (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2024)
The variety of different activities in Islamic boarding schools creates a variety of learning cultures that are very different from schools in general. The differences in student learning cultures are an interesting matter that is worth studying in depth. This research aims to explore the learning culture of Islamic boarding school students. The approach used is a qualitative approach with descriptive methods. This research involved seven students from various Islamic boarding schools in the Special Region of Yogyakarta as subjects. The results of this research explain various students’ learning cultures, including social culture in the Islamic boarding school environment, spiritual values in students’ motivation, students’ interactions in social groups, students’ learning methods and activities, the influence of figures as role models, and learning from experience. Guidance and counseling play an important role in supporting the development of students at Islamic boarding schools. Scientific implications include understanding social and cultural contexts, adapting to individual learning styles, developing social and emotional skills, strengthening spiritual values, and developing student identity and character.